An early start for EU reform: Germany's options for the 2008/09 revision of the European financial constitution - Peter Becker (Stiftung Wissenschaft und Politik (SWP), 2007)
On April 4th, 2006, the European Union agreed on a new Financial Framework for the 2007-13 annual budgets. The compromise was reached under very difficult political and economic circumstances, and it is more than doubtful whether the existing funding and budget system will be able to keep the Union functioning effectively in future and whether the current structure of the EU's budget can cope with the coming challenges. One integral part of the agreement was commitment to a comprehensive revision of the system. The goal and purpose of this debate, which is scheduled for 2008/09, is a thorough overhaul of the EU's financial constitution, examining both the revenue and expenditure sides. A significant factor for the outcome of the revision debate could turn out its timing, which coincides with the discussion about reducing the size of the Commission and appointing new members.The discussion about the substance and goals of revision began this spring with the European Parliament's Lamassoure Report on reform of the EU's own resources system. Germany will have to decide whether to take a stance at an early stage in this revision debate to influence the formulation of priorities and the timetable of the debate in its own interests. The purpose of German policy should be to foster solutions that focus the EU budget more strongly on funding shared public goods. (SWP Research Papers)
Keywords: 320